On the art of psychoanalytic listening in a group - Kardaras, Konstantinos (Psychology: the Journal of the Hellenic Psychological Society, 2026)
The book "Whispers of Words: Psychoanalytic Listening in a Group" by Klimis Navridis is a continuation and refinement of his previous work on the psychodynamic approach to groups, enriching the theory with contemporary references and extensive clinical experience. The central theme of the book is the psychoanalytic "listening" of the group, not as a sum of individuals but as a multi-person inter-subjective bond, according to the thinking of René Kaës. The author attempts to clarify experientially what it means to "listen" to a group, using rich clinical examples and metaphors, such as that of an orchestra, which highlight the musicality, rhythm, and tonality of group becoming. The book is organized into 30 short chapters, which can be read independently, but follow a clear logic of transition from theory to clinical practice. Of particular importance is the author’s attitude, who, through sincere self-revelation, doubt, and recognition of the analyst’s "negative capacity," deconstructs the therapist’s omnipotence and presents a deeply human and authentically psychoanalytic position. The work is aimed at both trainees and experienced therapists, offering a lively, thoughtful, and essentially instructive journey into psychoanalytic work with groups.